State of production, vegetable consumption, and seed production of vegetable crops in Russia; and problem of food security - V.F. Pivovarov; S.M. Sirota; P.F. Kononkov (Овощи России, 2009)
Horticulture is one of the sectors of the national economy that play a key role in supplying people the food of high biological value. It is very important how this sector covers people's requirements in food of therapeutic value because it provides the basis of people health, their working capacity, high life span, and, as consequence, economic and political independence of Russia.